Strategies to improve the implementation of policies, practices or programmes in sporting organisations targeting poor diet, physical inactivity, obesity, risky alcohol use or tobacco use: a systematic review - McFadyen, Tameka (BMJ Open, 2018)
OBJECTIVES: The primary aim for this review is to determine the effectiveness of strategies to improve the implementation of policies, practices or programmes in sporting organisations. The secondary aims are to describe the cost or cost-effectiveness and adverse effects of such strategies and to examine the effects of those implementation strategies on individual’s diet, physical activity, obesity, alcohol use or tobacco use. METHODS: We conducted searches of academic databases (eg, MEDLINE, EMBASE and CENTRAL), trial registers and hand searches of selected journals. Studies were included if they were conducted at a sporting venue; described a strategy to improve implementation of policies, practices or programmes focusing on one or more health risks (diet, physical inactivity, obesity, alcohol or tobacco use), and included a parallel control group. Two authors independently screened citations and extracted data. The results of included studies were synthesised narratively. RESULTS: Of the 5926 citations screened three studies met the inclusion criteria. Two studies were randomised controlled trials. Two studies sought to improve the implementation of nutrition-related policy and practices and one study sought to improve implementation of alcohol-related policy and practices. Each study reported improvement in at least one measure of policy or practice implementation. Two studies reported individual-level outcomes and found a reduction in excessive alcohol consumption and an increase in purchase of fruits and vegetables at the sports club ground. Two studies assessed club revenue as a potential adverse effect, neither reported significant between-group differences on these measures. CONCLUSION: There is a sparse evidence base regarding the effectiveness of strategies to improve the implementation of policies, practices or programmes targeting chronic disease risk factors in sporting clubs. While all studies reported some improvements in implementation, for some multistrategic implementation strategies it is difficult to determine the extent to which such effects are generalisable. PROSPERO REGISTRATION NUMBER: CRD42016039490.